The Role of Riau Malay Culture-Based Ethnoscience on the Character Formation of Elementary School Students - Viony Syafitra; Wilasari Arien; Lutfiana Arbiah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Character education is a foundational aspect of elementary education, particularly when aligned with local cultural values. Ethnoscience, as a form of traditional knowledge rooted in local wisdom, offers potential for contextualizing moral and social learning. This study explores how Riau Malay culture-based ethnoscience contributes to the character formation of elementary school students. This qualitative research was conducted over six months (January–June 2025) at an elementary school in West Maredan Village, Perawang. Data were collected through participatory observation, in-depth interviews with school principals, teachers, and 36 students from grades IV to VI, as well as documentation of learning processes. Data were analyzed using Miles and Huberman's interactive model. Findings reveal that integrating Riau Malay ethnoscience—through folklore, proverbs, local practices, and environmental customs—effectively supports the development of students’ religiosity, responsibility, social care, and ecological awareness. Observable changes included increased participation in collective prayers (from 60% to 88%), mutual cooperation (45% to 78%), and proper waste sorting (40% to 75%). The integration of ethnoscience into classroom activities contextualizes character education and bridges academic learning with students’ lived cultural experiences. This model aligns with the Pancasila Student Profile and demonstrates that cultural-based learning can foster sustainable character development in early education.